6.4k views
4 votes
If f(x)=2x²+3x-1 and g(x)= -x, then f(-1)+g(-1) = __

User Dmoebius
by
4.7k points

1 Answer

4 votes

SOLUTION

STEP 1: Write the given functions


\begin{gathered} f(x)=2x^2+3x-1 \\ g(x)=-x \end{gathered}

STEP 2: Find f(-1)+g(-1)

We find f(-1) first,


\begin{gathered} Substitute\text{ }-1\text{ }for\text{ }x\text{ }inf(x) \\ 2(-1)^2+3(-1)-1=2-3-1=2-4=-2 \end{gathered}

We find g(-1),


\begin{gathered} g(x)=-x \\ substitute\text{ -1 for x in g\lparen x\rparen} \\ g(-1)=-(-1)=1 \end{gathered}

Find the required function,


f(-1)+g(-1)=-2+1=-1

Hence, the answer is -1

User Nktoronto
by
4.9k points